Effect Of Salt Concentration On Morphology And Mechanical Properties Of Polyurethane-Bioglass Composite Scaffold - Abidin, Muhamad Firdaus Zainal (Universiti Sains Malaysia, 2017)
The aim of tissue engineering is the fabrication of three-dimensional scaffolds that can be used for the reconstruction and regeneration of damaged tissues and organs. A broad variety of techniques have been developed to create either fibrous or porous scaffolds from polymers, metals, composite textiles and ceramics. Nevertheless, the most promising materials are biodegradable polymers due to their comprehensive mechanical properties, ability to control the rate of degradation and similarities to natural tissue structures. In this study, porous bioactive glass (BG) reinforced polyurethane (PU) composite scaffolds with different salt ratio was fabricated by using salt leaching technique as this method does not involve any high temperature process that will affect the properties of the polymer. One of the factors that determine the properties of the scaffold is the porosity. Salt concentration is one of the parameters that influence the porosity. Various salt concentration were used with the aim of optimizing the pore network and to obtain the optimum mechanical properties of scaffolds. The chemical and physical properties of the fabricated porous scaffolds were examined by several characterization techniques including Scanning Electron Microscopy (SEM), Thermogravimetric Analysis (TGA), Fourier Transform Infrared Spectroscopy (FTIR), and compressive strength test. Composite scaffolds with low amount of porosity shows a better compressive strength and modulus. Overall, composite scaffolds with salt ratio 1:3 consists of pore which was homogeneously distributed and have the highest compressive strength.